2002
DOI: 10.3354/meps226165
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for density-dependent mortality in recruitment of a temperate reef fish, cunner Tautogolabrus adspersus, among similar reefs in the vicinity of an anthropogenic disturbance

Abstract: Determining the factors that regulate recruitment of cunner Tautogolabrus adspersus, a temperate reef fish, can help assess the effect of an anthropogenic disturbance on population abundance. The relative abundance of cunner recruits was tracked over 1 reproductive season via visual counts on line transects across similar habitats at 4 sites across 3 boulder reefs in the vicinity of the Pilgrim Nuclear Power Station (PNPS) in Plymouth, Massachusetts, USA. Habitat characteristics including macroalgae structure,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
1
3
0
1
Order By: Relevance
“…Thus, periods of above‐average growth may allow females to invest more energy in reproduction (Harvey, 2005), either producing more or larger eggs, perhaps resulting in the ‘carry over’ effect we detected. Our observation that density‐dependent mortality appeared to occur during the settlement period was consistent with experimental research on population dynamics in demersal fishes on temperate and coral reefs showing that, at least locally, density‐dependent mortality occurs in the period shortly after settlement (Hixon and Carr, 1997, Anderson, 2001; Nitschke et al. , 2002; Hixon and Jones, 2005, Johnson, 2006).…”
Section: Discussionsupporting
confidence: 89%
“…Thus, periods of above‐average growth may allow females to invest more energy in reproduction (Harvey, 2005), either producing more or larger eggs, perhaps resulting in the ‘carry over’ effect we detected. Our observation that density‐dependent mortality appeared to occur during the settlement period was consistent with experimental research on population dynamics in demersal fishes on temperate and coral reefs showing that, at least locally, density‐dependent mortality occurs in the period shortly after settlement (Hixon and Carr, 1997, Anderson, 2001; Nitschke et al. , 2002; Hixon and Jones, 2005, Johnson, 2006).…”
Section: Discussionsupporting
confidence: 89%
“…This result led them to conclude that habitat‐mediated post‐settlement processes are critical to recruitment and population dynamics of cunner. In a similar study in coastal Massachusetts, Nitschke et al (2002) found strong evidence for density‐dependent mortality in the post‐settlement phase and that small changes in habitat structure across reefs over the recruitment season can lead to variability in recruitment. Thus, reefs that decreased in complexity experienced higher cunner mortality.…”
Section: Cunnermentioning
confidence: 88%
“…In such cases, there can be strong density‐dependent increase in agonistic activity with increasing density of conspecifics, leading to increased predation risk and density‐dependent mortality at high densities. Indeed, one of the first attempts to test foraging arena predictions involved a small benthic fish (cunner, Tautogolabrus adspersus ), which has exhibited exactly such increase in activity and mortality when its densities were experimentally manipulated or varied among reef sites (Nitschke et al. 2002; Juanes 2005).…”
Section: Mechanisms That Cause Prey Population Partitioning and Vulnementioning
confidence: 99%